Integration of Sustainability and SCOR Model in Sustainable Halal Tourism Competitiveness: Integrasi Keberlanjutan dan Model SCOR dalam Daya Saing Pariwisata Halal Berkelanjutan - Hana Catur Wahyuni; Lusia Permata Sari Hartanti; Inggit Marodiyah; Wiwik Widhianingsih (Academia Open, 2025)
General Background: Halal tourism represents a growing segment in the global tourism industry, integrating Islamic principles with sustainable practices aligned to social, economic, and environmental dimensions. Specific Background: In Indonesia, particularly in Sidoarjo Regency, the halal tourism sector is emerging as a strategic driver of local competitiveness and community empowerment; however, its operational sustainability framework remains underdeveloped. Knowledge Gap: Previous studies rarely integrate sustainability principles with supply chain performance models to evaluate halal tourism competitiveness. Aims: This study aims to integrate the concept of sustainability with the Supply Chain Operations Reference (SCOR) model to assess and strengthen sustainable halal tourism competitiveness in Sidoarjo. Results: Using a descriptive–quantitative approach with 26 respondents, findings reveal high sustainability scores across all pillars—social (4.15), economic (4.20), and environmental (4.13)—with a total sustainability index of 4.16. The economic pillar is most dominant due to strong regulatory support and inter-sectoral collaboration. Novelty: The study introduces a hybrid SCOR–Sustainability framework that operationalizes the halal value chain through the five SCOR processes (Plan–Source–Make–Deliver–Return). Implications: The integration model provides an effective tool for policymakers and tourism stakeholders to harmonize operational efficiency, social responsibility, and environmental stewardship in sustainable halal tourism development. Highlights: Integrates sustainability principles with the SCOR framework for halal tourism. Identifies the economic pillar as the strongest driver of competitiveness. Proposes a practical model aligning efficiency, ethics, and environmental care. Keywords: Halal Tourism, Sustainability, Scor Model, Competitiveness, Value Chain